Keeping the light on - Nursing history center in Ceará - NUDIHMEn - Silvia Maria Nóbrega-Therrien; Maria de Irismar Almeida; Roberlandia Evangelista Lopes; Andréa da Costa Silva; Emanoela Therezinha Bessa Mendes; Sun-Eiby Siebra Gonçalves
ABSTRACT Objective: To share the implementation of the Center for Documentation, Information, History and Memory of Nursing in Ceará - NUDIHMEn and its achievements in caring for, producing and preserving the history and the memory of Nursing in Ceará. Method: It is an experience report regarding the work carried out in NUDIHMEN from 2009 to 2017. Results: The NUDIHMEn holds a database of 1,454 newspaper articles, mapped data of 35 manuscript volumes of the Ecclesiastical History of Ceará about Nursing precursors, in addition to 23 minutes books from the Fortaleza Santa Casa (1879 to 1970), documentation belonging to the São Vicente de Paulo Nursing School, 8 scanned minutes books from the UECE Nursing Course, among other research resources. Conclusion: The NUDIHMEn provides records on Nursing history in Ceará for knowledge, socialization and scientific production of the community concerned.